Narrowing the Climate Field: The Symbolic Power of Authors in the IPCC's Assessment of Mitigation. Issue 6 (31st August 2017) - Hughes, Hannah Rachel; Paterson, Matthew
Abstract: This article provides a critical analysis of the Intergovernmental Panel on Climate Change (IPCC) as a boundary organization using Bourdieu's concepts of field, habitus, and symbolic power. The article combines quantitative, network, and survey data to explore the authorship of Working Group III's contribution to the IPCC Fifth Assessment Report (AR5). These data reveal the dominance of a small group of authors and institutions in the production of knowledge that is represented in the AR5 report, and illuminates how the IPCC's centrality to the field of climate politics is shaping the research and publication strategies of researchers within that field. As a result, the study is able to identify organizational avenues for deepening the involvement and symbolic power of authors from the global South in IPCC assessments of climate change. While empirically, the results of this study lead us to question the IPCC as an assessor of knowledge, theoretically, it suggests that particularly in the international sphere, the use of the boundary organization concept risks overlooking powerful networks of scientific actors and institutions and their broader implication in the politicization of science.